A gold(i)-catalysed approach towards harmalidine an elusive alkaloid from Peganum harmala. Issue 41 (21st September 2022) - Miaskiewicz, Solène; Weibel, Jean-Marc; Pale, Patrick; Blanc, Aurélien
Abstract : Upon gold catalysis, the 2, 3-dihydropyrrolo[1, 2- a ]indole motif, encountered in few but interesting bioactive natural products, was efficiently obtained from N -aryl 2-alkynylazetidine derivatives. Abstract : Upon gold catalysis, the 2, 3-dihydropyrrolo[1, 2- a ]indole motif, encountered in few but interesting bioactive natural products, was efficiently obtained from N -aryl 2-alkynylazetidine derivatives. In an attempt to apply this methodology to the synthesis of harmalidine, isolated from the seeds of Peganum harmala, advanced amino 2, 3-hydropyrrolo[1, 2- a ]indol(one) derivatives were readily obtained in only 11 steps from but-3-yn-1-ol. While the reported structure of harmalidine could not be reached from these intermediates, a surprising 12-membered diimino dimer was isolated. Extensive comparison of the reported harmalidine NMR data to the experimental and calculated data of our synthetic molecules, harmaline or the synthetised N -methylharmaline show discrepancies with the proposed natural product structure.